176k views
5 votes
What is the recursive formula for this geometric sequence?

-3, -21, -147, -1029, ...

2 Answers

3 votes


a_(n+1) =7a_(n).

If we know the term
n^(th) and the common relation, r, of a geometric sequence, you can find the term
(n+1)^(th) using the recursive formula
a_(n+1) =a_(n).r.

The first term of the geometric sequence is a₁ = -3.

The common relation we have to find the relationship between a term and the term that precedes it.


r=(-21)/(-3) = 7

The recursive formula is:


a_(1) =-3


a_(n+1) =7a_(n)

User Chris Garrett
by
5.9k points
5 votes


a_1=-3\\r=7\\a_n=a_(n-1)\cdot r\\\\ \boxed{a_n=7a_(n-1)}

User Jeff Beck
by
5.7k points